2014
DOI: 10.3163/1536-5050.102.1.010
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health record: integrating evidence-based information at the point of clinical decision making

Abstract: The authors created two tools to achieve the goals of providing physicians with a way to review alternative diagnoses and improving access to relevant evidence-based library resources without disrupting established workflows. The “diagnostic decision support tool” lifted terms from standard, coded fields in the electronic health record and sent them to Isabel, which produced a list of possible diagnoses. The physicians chose their diagnoses and were presented with the “knowledge page,” a collection of evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Librarians’ participation lies primarily in implementing systems, creating links to the medical literature, and using EMRs to provide patient health information. For health providers, clinical decision support systems enable them to effectively support their evidence-based practice with the involvement of health sciences librarians who manage and retrieve data and information from patient EMRs [ 32 , 36 ]. Those librarians may also be asked to devise “research evaluation support services” to support evidence-based practices and increasing demand to assess research output and impact [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Librarians’ participation lies primarily in implementing systems, creating links to the medical literature, and using EMRs to provide patient health information. For health providers, clinical decision support systems enable them to effectively support their evidence-based practice with the involvement of health sciences librarians who manage and retrieve data and information from patient EMRs [ 32 , 36 ]. Those librarians may also be asked to devise “research evaluation support services” to support evidence-based practices and increasing demand to assess research output and impact [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Priority issues identified are consistent with those documented in the literature, particularly as related to the limited community services impacting community integration, 17 limited clinician access to SCI guidelines and tools, 13 limited use of technology to support communication between family physicians and specialists, 18 limited care integration and coordination across sectors, 19 and lack of infrastructure support for SCI care. 20 Similarly, there is some evidence to support the implementation of proposed solutions such as the establishment of key stakeholder networks 21 and CoPs 22 to advance research and care, use of electronic platforms to improve collaboration and communication, 23 development of clinical support tools integrated into EMR software, 24 and use of patient empowerment frameworks to support self-management. 25,26 These solutions are well aligned with the Patients First: Action Plan for Health Care -Ontario's plan for changing and improving Ontario's health system, emphasizing the role of patients at the centre of the system, focusing foremost on their needs.…”
Section: Discussionmentioning
confidence: 99%
“…EMRs were perceived as a strength and opportunity to facilitate EBM. A growing number of studies have reported the role of EMR in facilitating evidence-based practice [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%